Composição e diversidade da macrofauna como indicadores da restauração do solo numa cronosequência de capoeiras e florestas na Amazônia Oriental - Silva, Paulo Rogério dos Santos (2012)
In Eastern Amazon, native ecosystems are rapidly destroyed and remnant primary forests are further cleared. Therefore, the information about biodiversity and natural processes of these remnants need to be saved urgently. Indeed, soil biota integrity is essential to maintain the productivity of natural and agriculture ecosystems and basic informations about the role of soil invertebrates in the provision of support ecosystem services are still missing. This study evaluated four main determinants of soil macrofauna composition and diversity (present soil use, micro-regions, soil use history, fire frequency) in the Belém endemism centre. Soil macrofauna was sampled in 8 young secondary forests (SF)(4-7 y), 6 medium SF (11-15 y), 7 “old” SF (20-40 y), 8 forest remnants and 3 pastures. Its composition and diversity were analysed through Principal Component and Between-class Analyses. Present soil use (forest age/pasture) explained at best 15% of macrofauna variance (classified by large taxonomic units) however, macrofauna communities were distinct between micro-regions (R2 =26%) and particularly affected by soil use history (R2 =32%). Predator abundance and richness decreased will past soil use intensity. These results are essentials to plan soil biological function and productivity restoration in Eastern Amazon.